An ecological network for large carnivores as a key tool for protecting landscape connectivity in the Carpathians - Kristýna Vlková; Vladimír Zýka; Cristian Remus Papp; Dušan Romportl (Journal of Maps)
The main aim of our study was to delineate a coherent ecological network for large carnivores, using a unified methodology, which would be flexible and serve as a basis for nature and habitat connectivity protection across the Carpathians. We applied a comprehensive methodological approach based on habitat suitability modelling followed by connectivity modelling. For the habitat suitability modelling, we used a robust set of large carnivores occurrence data, which allowed us to build a solid model. From the model, we derived a layer of patches of suitable habitat of required quality and resistance surface to express landscape permeability. Both outputs were crucial for the connectivity modelling. We applied Random Walk and Least-Cost Path models and combined them to determine feasible connections between suitable habitats. With expert discussions and editing/improvement of modelled corridors, we developed a unique ecological network consisting of various components adapted to the heterogeneity of the Carpathian landscape.